PENGARUH METODE STORYTELLING TERHADAP KETERAMPILAN BERBICARA SISWA KELAS V DALAM PEMBELAJARAN BAHASA INDONESIA SDS PELITA KASIH SINGKAWANG - melinia, Lepiana; fitriyadi, slamat; setya novanto, yogi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Abstract. This study aims to 1) find out how the students' speaking skills are before applying the storytelling method of class V of Pelita Kasih Elementary School, Singkawang: 2) find out whether the storytelling method can improve the speaking skills of class V students of Pelita Kasih Elementary School, Singkawang: 3) find out the effect of the storytelling method on the speaking skills of class V students of Pelita Kasih Elementary School, Singkawang. The type of research used is quantitative with a one group pre-test-post-test research design. The population in this study were all class V students of Pelita Kasih Elementary School, Singkawang, totaling 23 students. The results of the study showed that 1) based on. data analysis that in the pretest data, the average score of the speaking skills test was 29. 2) there was an increase between the pretest that did not apply the storytelling method with an average score of 29, while the posttest data score that applied the storytelling method got an average score of 56, so from that there was an increase in the average score of speaking for grade V students. 3) The test of the effect size of the storytelling method on helping students, the results were influential with the effect size results being very high with a value of 3.47 at a distance of ES> 2.0. The implications of this study indicate that the need for a storytelling method in learning Indonesian to improve students' speaking skills so that it can have a positive impact on Indonesian speaking skills. Keywords: Influence, model, storytelling, speaking skills.